1997
DOI: 10.1111/j.2044-8309.1997.tb01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in aggression: Does social representation mediate form of aggression?

Abstract: In contrast to the usual pattern of higher male aggression, girls have been shown to exceed boys on frequency measures of indirect aggression. Women also tend to view aggression in terms of an expressive social representation whereby it is seen to result from loss of self‐control, in contrast to men who tend to describe it as an instrumental act aimed at exerting control over others. Sixteen items measuring different forms of aggressive behaviour were given to 105 undergraduates together with Expagg, a psychom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 19 publications
5
47
0
3
Order By: Relevance
“…It is interesting that we found physical and verbal victimization to be separable factors because some previous work has shown that verbal and physical forms of direct victimization constitute a single dimension [see, e.g., Björkqvist et al, 1992;Campbell et al, 1997]. The reason for this might be that whereas we used oblique rotation, the previous studies used orthogonal rotation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is interesting that we found physical and verbal victimization to be separable factors because some previous work has shown that verbal and physical forms of direct victimization constitute a single dimension [see, e.g., Björkqvist et al, 1992;Campbell et al, 1997]. The reason for this might be that whereas we used oblique rotation, the previous studies used orthogonal rotation.…”
Section: Discussionmentioning
confidence: 82%
“…For example, it has been suggested that direct victimization might be better split into verbal and physical forms of aggression, although the statistical separability of verbal and physical victimization remains uncertain [see Bjorkqvist et al, 1992;Campbell et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…The present instructions did not specify that the aggressive acts had occurred when the person was angry. Some of the previous selfreport measures of indirect aggression have followed the original peer-reports of children's indirect aggression [Lagerspetz et al, 1988] in specifying that the act has to have occurred when the person was angry [e.g., Richardson and Green, 1999], whereas others [e.g., Campbell et al, 1997] have not.…”
Section: Discussionmentioning
confidence: 99%
“…A primary example of such a scale is the Conflict Tactics Scale [CTS: Straus, 1979], which measures acts of physical (and other forms of) aggression between partners [Archer, 1999[Archer, , 2000[Archer, , 2002. Comparable act-based scales measuring aggression between non-partners, or more generally, have been used in a range of studies over the previous 25 years: e.g., the Olweus Multifacited Aggression Scale [OMAI: Olweus et al, 1980]; the Interpersonal Behavior Scale [Mauger et al, 1980]; and the Self-Reported Aggressive Behaviour scale [Campbell et al, 1997]. The Richardson Conflict Response Questionnaire [RCRQ: Green et al, 1996;Richardson and Green, 1999] is based on earlier scales, and was explicitly designed to measure both direct and indirect forms of aggression.…”
Section: Introductionmentioning
confidence: 99%
“…From a different angle, this can be related to the dimension of irrationality, deviance, transgression or evil in female violence to which Naylor (2001) refers as dominant, as well as to the findings of Campbell and collaborators (Campbell et al 1997;Campbell et al 1999) which show female violence as an expression of mood, i.e. caused by a loss of control, by irrationality or senselessness, in contrast to male violence, which is shown as instrumental, a way to impose control on others, above all as a reaction to failing to reach goals.…”
Section: Discussionmentioning
confidence: 99%